LEARNING PROCESSES IN BUSINESS RELATIONSHIP DEVELOPMENT - Sulhaini . (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2008)
The paper explores business relationship development between small English firms with its five customers in Indonesia, which has become an uncertain market since 1997. The study utilised qualitative method and followed inductive logic to explore the phenomena. The data was gathered through in-depth interviews both in England and in Indonesia with the Sales Director, the Export Manager, the Company Secretary and the Purchasing Manager of the buying firms. The finding suggests critical roles of learning in maintaining competitiveness in an uncertain market. Learning processes underline the development of business relationship elements, which then influence the development the business relationships.